Influencia de harinas de yuca y de batata sobre pigmentación, contenido de carotenoides en la yema y desempeño productivo de aves en postura - Posada, C.A.; López, A.; Ceballos, H. (2006)
Utilization effect of cassava (Manihot esculenta) and potatoe (Ipomoea batatas) on pigmentation, carotenoids pull on egg yolk and performance yield hens. Eight diets (T1:without pigment, T2: commercial pigment, T3: cassava meal 15%, T4: cassava meal 30%, T5: sweet potato meal 15%, T6: sweet potato meal 30%, T7: cassava and sweet potato meal 15% each, T8: cassava and sweet potato meal 25% each) in a randomized design using four replicates of three hens each during seven experimental periods were evaluated. Diets were iso-energetics (2.9 kcal/g) and iso-proteis (14.5% CP). Carotenoid concentrations (UV-visible chromatography) had differences (P<0.01) among diets. Pigmentation (Fan Roche) and carotenoid concentration in egg yoks to come from cassava and sweet potato diets did not show differences (P>0.05) A comparison with egg yolk to come from test diets significant differences (P<0.01) were detected. Diet with commercial pigment showed the highest pigmentation and carotenoid concentration in egg yolk.The other hand, there saw not differences (P>0.05). A comparison with egg yolk to come from test dietssignificant differences (P<0.01) were detected. Diet with commercial pigment showed the highest pigmentation and carotenoid concentration in egg yolk. The other hand, there saw not differences (P>0.05) between egg yolk to come from diet without pigment and cassava and sweet potato diets. Lutein, -carotene, -carotene, and 9-cis- - carotene were the most importants carotenoids found in diets and egg yolk (HPLC). Cantoxatin was found in egg yolk and diet with commercial pigment only. Its concentrationreached to 65% in profile carotenes. Lutein was the main carotenoid in egg yolk, while -carotene was the highest in all diets. Egg yolk that come from cassava and sweet potato 15% diet, showed the highest Retinol Equivalent provitamin A. Type and component egg, don't showed differences (P>0.05). There were differences (P<0.01) in yield performance.